Human Resources Management Strategy in the Military Justice Environment: Study of State Civil Apparatus Management at the High Court of the Supreme Court of the Republic of Indonesia - Zidny Taqiyya; Asropi; Ratri Istania (GoAcademica Research & Publishing, 2023)
The Supreme Court is a judicial institution vested with authority to exercise judicial power in four separate branches of the judiciary, namely the General Courts, Religious Courts, Administrative Courts, and Military Courts. The Military Court, in particular, serves as the judicial body responsible for upholding the law and justice for members of the Indonesian National Armed Forces (TNI). Unlike the other three branches of the judiciary, the Military Court system consists of three appellate courts and one main court. The existence of these four courts is governed by Law Number 31 of 1997 on Military Judiciary and the Chief Justice of the Supreme Court Regulation Number 125 of 2009 on the Delegation of Authority to High-Ranking Officials and Chief Justices of Appellate Courts within the Supreme Court for Signing in the Field of Personnel. However, the implementation of these regulations has still resulted in varying interpretations and paradigm differences, especially in understanding the phrase